2006
DOI: 10.1136/thx.2005.047332
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal pulmonary function of childhood bronchiectasis and comparison with cystic fibrosis

Abstract: Background: Little has been published on the progression of non-cystic fibrosis bronchiectasis (BX), especially in childhood. Data are needed for prognosis and evaluation of the effectiveness of treatments. A study was undertaken to evaluate the change in lung function over time in children with BX, and to consider covariates and compare them with the local cystic fibrosis (CF) population. Methods: Children with BX or CF and >3 calendar years of lung function data were identified from hospital clinics. Diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
3
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 32 publications
6
46
3
2
Order By: Relevance
“…Although there has been limited longitudinal research focused on bronchiectasis determinants in patients with CF (4), cross-sectional and short-term studies suggest that bronchiectasis correlates with significantly increased airways obstruction (8,9). In addition, Evans et al (6) reported that patients with bronchiectasis "who become colonized by P aeruginosa have poorer lung function when first colonized than those colonized by other organisms."…”
mentioning
confidence: 99%
“…Although there has been limited longitudinal research focused on bronchiectasis determinants in patients with CF (4), cross-sectional and short-term studies suggest that bronchiectasis correlates with significantly increased airways obstruction (8,9). In addition, Evans et al (6) reported that patients with bronchiectasis "who become colonized by P aeruginosa have poorer lung function when first colonized than those colonized by other organisms."…”
mentioning
confidence: 99%
“…66,67 La evolución de la función difiere según la etiología. Así, pacientes con FQ presentan un descenso más rápido de la función que los no FQ, 68 …”
Section: Tabla 3 Situaciones En Las Que Es Recomendable Investigar Lunclassified
“…Bronquio cortado transversalmente con vaso adyacente aunque en ambos se produce su deterioro con el tiempo, con presencia mayoritaria en la edad adulta de un patrón obstructivo. 68 Las indicaciones de fibrobroncoscopía incluyen: afectación de un solo lóbulo pulmonar, cultivo de esputo repetidamente negativo sin respuesta al tratamiento, TACAR compatible con micobacterias atípicas con cultivos de esputo negativos, sospecha de aspiración pulmonar crónica y niños gravemente enfermos para obtener información microbiológica.…”
Section: Figura 1 Imagen En Vía De Tren Bronquio Dilatado Cortado Lunclassified
“…Both adults and children have been shown to develop progressively worsening airfl ow obstruction [42][43][44]. As bronchodilation is the key diagnostic feature, bronchiectasis is often not considered to be an obstructive lung disease.…”
Section: Lung Functionmentioning
confidence: 99%